Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/pr8101207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydration Layer on the Adsorption of Dodecane Collector on Low-Rank Coal: A Molecular Dynamics Simulation Study

Abstract: The hydration layer has a significant effect on the adsorption behavior of reagents during the flotation process of low-rank coal. Understanding the effect of hydration layer on the adsorption of common collectors on low-rank coal is a prerequisite for proposing a new enhanced coal floatation method. In this study, a smooth low-rank coal surface model with a density of 1.2 g/cm3 was constructed and compared with the XPS results. Three different systems, coal-water, coal-collector, and coal-water-collector, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Introducing Equations (7) and (8) into Equation (6), the change in the total Gibbs free energy of the solid-water adhesion is as follows:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing Equations (7) and (8) into Equation (6), the change in the total Gibbs free energy of the solid-water adhesion is as follows:…”
Section: Theorymentioning
confidence: 99%
“…The high oxygen content, especially the abundance of polar groups (phenolic/alcoholic hydroxyl, carbonyl, carboxyl, ether, and methoxyl), results in the poor floatability of coal [4][5][6][7]. These hydrophilic functional groups weaken the surface hydrophobicity of low rank coal via absorbing water molecules to form hydration film [8]. Moreover, some weakly acidic groups (phenolic OH and COOH) ionize in solution making the coal surface negatively charged [9].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic properties and reactivity of minerals’ surfaces can readily be altered in an aqueous environment, leading to different adsorption properties compared to dry surfaces. , ,, , For instance, DFT calculations showed that the water hydration layer on the smithsonite weakens the hybridization of s and p orbitals and lowers the electrophilicity of Zn atoms on the outermost mineral layer, subsequently reducing the interaction levels of smithsonite with carboxyl collectors . As further confirmed by DFT, hydration of sphalerite significantly alters the mineral surface properties through localization of Zn 3 d , 4 s , and 4 p orbitals, resulting in a reduction in the reactivity of Zn atoms and, ultimately, the Zn-xanthate collector interactions .…”
Section: Applications Of Molecular Modeling To Froth Flotationmentioning
confidence: 92%
“…With the continuous development of computer technology, molecular simulation is increasingly applied to study the micromechanism of coal surface wettability. This approach has gradually become an important method in the field of coal flotation [20][21][22][23]. Zhao [24] revealed the significant effects of carbon and oxygen elements in coal on the wettability of coal dust.…”
Section: Introductionmentioning
confidence: 99%